Pengembangan Media Pembelajaran Matematika Interaktif Berupa Aplikasi Android Menggunakan Kodular Pada Materi Relasi dan Fungsi Untuk Siswa Kelas VIII SMP - Arnaz, Anisa; Wahyuni, Yusri; Khairudin, Khairudin; Fauziah, Fauziah (PHI: Jurnal Pendidikan Matematika, 2022)
This development research was motivated by: (1) The use of IT-based math learning media at SMPN 3 Ulakan Tapakis has not been varied. (2) Students look less active during the learning process. (3) There is a potential, where the widespread use of smartphones among students is caused by the distance learning process, but so far there are still schools that have not utilized this potential for learning facilities at school. (4) Based on the results of the analysis of the mathematics UAS scores of class VIII SMPN 3 Ulakan Tapakis, the highest percentage of students answering incorrectly is in the number of questions about relations and functions. (5) One website for creating android applications without the need to understand programming languages is Kodular. The purpose of this study was to produce interactive mathematics learning media in the form of android applications using Kodular on relation and function material that is valid and practical for grade VIII junior high school students. The development procedure refers to Luther Sutopo's multimedia development model which researchers modified into 5 stages, namely the concept stage, design, material collection, manufacture and trial stage. Based on the validity test and practicality test that has been carried out, the overall validity value is 91.67% with very valid criteria, and the practicality value is 98.7% with very practical criteria. So it can be concluded that this interactive math learning media on relation and function material is valid and practical as a math learning media.